Competency-based approach and competencies in higher education: a theoretical review - Kulik, Andrey A. (2020)
Economic changes not only in the country, but also on the world labor market explain the growing demands on young professionals. New requirements for the model and quality of the graduate appear, and new approaches to their competitiveness and effectiveness appear. The authors analyzed the concepts of a competency-based approach, competence, developed characteristic features and the field of implementation of these definitions in higher education. It has been established that a qualitatively new mission, tasks and content of modern education in the new conditions should be focused not only on fundamental knowledge, but also on the formation of practically oriented skills and competencies.